Mechanism of Anticancer Effects of Antimicrobial Peptides (Journal of Fiber Bioengineering and Informatics, 2015)
Antimicrobial Peptides (AMPs) were first known as a group of innate immune products that mainly\rtargets on the invading pathogens among multiple species. The essential mechanisms of action of AMPs\rtoward microbial cells have been reported as electrostatic attraction and hydrophobic interaction between\rAMPs (cationic AMPs) and microbial cell membranes. These effects also contribute to the potential\rmechanism of anticancer activities of AMPs as well. The membrane difference between cancer cells\rand normal cells are believed to play significant roles in AMPs orienting process. Membrane selective\rtargeting properties make AMPs promising candidates for alternative approach to solve the problems\rfrom anticancer drug resistance.